Local Culture in Indonesia As Risk of Child Sexual Abuse: A Systematic Review - Solehati, Tetti; Salsabila, Azzahra; Nurafni, Ratu; Millenika, Valencia Trie; Rindiarti, Nadia Amelia; Adila, Raisa; Hermayanti, Yanti; Kosasih, Cecep Eli; Mediani, Henny Suzana (Universitas Aisyah Pringsewu, 2021)
Introduction: Sexual issues in Indonesia are never discussed openly in the family, one of the contributing factors is the presumption of taboo culture in the conversation of sexual topics. This can be a risk of sexual abuse in children. Objective: To identify the cultural diversity of Indonesia at risk of child sexual abuse. Method: We conducted systematic reviews using PubMed, Science Direct, SpringerLink, EBSCO for the keywords